Are small renal masses all the same?. (23rd March 2020) - Tan, Yu Guang; Khalid, Mohamad Farhan Bin; Villanueva, Andre; Huang, Hong Hong; Chen, Kenneth; Sim, Allen Soon Phang
Abstract : Objectives: To evaluate variables that can predict synchronous metastasis in patients presenting with small renal masses. Methods: We reviewed our institution's prospectively maintained database of 565 patients diagnosed with small renal masses (≤4 cm) over a 16‐year period. Variables associated with synchronous metastasis and subsequent relapse were analyzed using χ 2 and logistic regression models. Results: A total of 16 patients (2.7%) presented with synchronous metastasis. Just three patients with tumor size <3 cm had metastatic disease at presentation. On multivariate analyses, tumor size >3 cm, symptomatic cancer, age >65 years and ipsilateral synchronous tumors were independent predictors of M1 renal cell carcinoma. A weighted predictive model (concordance index 0.786) showed that a score ≥2 significantly increases the risk of synchronous metastasis (7.9% vs <1% for score <2, P < 0.01, hazard ratio 12.56, 95% confidence interval 5.52–22.85). A total of 498 (90.7%) patients underwent nephrectomies, 27 (4.9%) had ablative therapies and 24 (4.4%) continued on active surveillance/watchful waiting. Over a median follow‐up period of 62.8 months, 30 patients (6.1%) had disease recurrence. On multivariate analyses, higher Fuhrman grade and lymphovascular invasion were independent predictors of recurrence. A separate predictive model (concordance index 0.723) showed that either pathological outcome increases recurrence risk up to 15% ( P < 0.01, hazard ratio 11.83, 95% confidence interval 5.82–18.76). Conclusions: Several clinical variables can better identify the metastatic potential of small renal masses. The two proposed predictive models can be valuable tools in future clinical practice.